Social stigmas towards people living with HIV in the Sars-CoV-2 vaccination process - Fernández-Silva, Carlos; Hernández-Pérez, Francisco; Vidal Vidal, Edgar (Universidad y Salud, 2022)
Introduction: Social stigmas in people living with Human Immunodeficiency Virus (HIV) have been part of their history and can still be identified in today's care environments. Objective: To analyze the social stigmas in relation to the care of people living with HIV by those who provide the anti Sars-CoV-2 vaccination service. Materials and methods: A descriptive quantitative research were developed that included a census sample of 126 people. The scale of social stigma in the care of people with HIV/AIDS (Acquired immunodeficiency syndrome) was applied. The information was analyzed through SPSS version 25. Results: Most of the participants reported not knowing people with HIV, but they have been treated as users (54%) and considered that they are discriminated (88.1%). Although a low level of stigma was evidenced (71.4%), these are present in 85.7%. Having had contact as a user with people with HIV was associated with the level of stigma (p=0.008). Conclusions: It is necessary to promote training in which the complexity of the phenomenon is addressed and aspects such as social stigmas are identified, incorporating the biopsychosocial paradigm together with a gender perspective in favor of the comprehensive provision of care.